DESCRIBING KITAB PERUKUNAN BESAR MELAYU BY ABDUL RASYID BANJAR FROM THE LETTER OF ALPHABET CONCEPT TO SYNTHESIS CONSTRUCTION - Zulfiana Amaliana MZ (ppjbsip, 2020)
As the spread of Islam in the archipelago, a manuscript found in 19th century AD entitled Perukunan Besar Melayu by Abdul Rasyid Banjar. It was about Fiqh which described using Bahasa and written in Arab-Melayu. So, it used as an object of research that categorized as a qualitative research with a philological descriptive approach. This study aims to describe 1) transliterated of the manuscript to obtain complete and clear editing, 2) compliances of spelled and punctuated, and 3) distribution of syntax. To achieve the research objectives, data analysis carried out using the philological work procedure techniques and comparative analysis. So, the result of this research is 1) transliterated of Arab-Melayu alphabet into Latin alphabet, 2) reconstruction of spelled and punctuated, and 3) syntactic reconstruction